Primary dedifferentiated liposarcoma of the gallbladder: a case report and literature review - Wang, Lan; Lin, Tingting; Hai, Yubin; Yu, Kai; Bu, Fan; Lu, Ji; Wang, Xiuli; Li, Miao; Shi, Xiaoju (Frontiers in Surgery, 2024)
BackgroundLiposarcoma (LPS) is a kind of malignancy of soft tissue usually found in the retroperitoneal, limb, or neck region, and some may be detected with delayed symptoms (pain or palpable mass), and less frequently occurs in organs of the digestive system. In contrast, Dedifferentiated liposarcoma (DDLPS) is a common histological subtype of LPS. The present study reported a case of dedifferentiated liposarcoma originating in the gallbladder. Differentiated liposarcoma originating from the gallbladder is rarely reported.Case descriptionA 64-year-old female patient presented to our hospital with a painless abdominal mass. Abdominal computed tomography (CT) showed that the gallbladder had lost its normal shape, and a 9.1 cm × 7.1 cm × 12.1 cm mass was seen in the area of the gallbladder fossa and the right upper abdomen below it, which had an irregular morphology, inhomogeneous density, and nodular calcification, with marked inhomogeneous enhancement on enhancement scan. Preoperative tumor markers and liver function indicators were not abnormal. With suspicion of a giant malignant tumor of the gallbladder, she underwent a cholecystectomy combined with abdominal mass resection. After surgery, the tumor and gallbladder, were completely resected, and postoperative pathological results confirmed the diagnosis of dedifferentiated liposarcoma deriving from gallbladder. After surgery, the patient and his family refused to continue treatment. After 15 months follow-up, the patient remains asymptomatic and does not show any signs of recurrence. And she is now under continued follow - up.ConclusionsTreatment of dedifferentiated liposarcoma is still at exploratory stage, and a lack of clinical evidence for this condition might hinder access to clinical trials and studies. Currently, the treatment of choice for dedifferentiated liposarcoma remains radical resection. In the available clinical studies, there are no robust data to support clinical use of neoadjuvant and adjuvant radiochemotherapy. As with other diseases, the use of radiotherapy and chemotherapy before and after surgery may be a potential future treatment.